Effects of Red Bean Flour Substitution (Phaseolus vulgaris L.) On making sweet Kue Simping On Physical Quality And Consumer Acceptability - Habsoh, Siti (Advances In Social Humanities Research, 2024)
This study investigates the potential of red bean flour substitution in enhancing the physical quality and acceptability of sweet Kue Simping, a traditional Indonesian snack. Conducted at the Pastry and Bakery Processing Laboratory of the Culinary Education Program, State University of Jakarta, from February 2022 to January 2024, the research employed an experimental approach. Sweet Kue Simping cakes were substituted with red bean flour at varying percentages of 5%, 10%, and 15%, and evaluated by 30 moderately trained panelists. Statistical analyses, including the Friedman test, revealed no significant effect of red bean flour substitution on the acceptability of sweet Kue Simping in terms of various sensory attributes. However, physical quality tests using ANOVA demonstrated a significant influence of red bean flour substitution on the diameter of sweet Kue Simping. Duncan's test further confirmed notable differences among the treatments. The study recommends utilizing a 5% substitution of red bean flour to develop sweet Kue Simping, offering a novel approach to diversify traditional snacks and potentially reduce reliance on tapioca flour. Furthermore, data collection and analysis techniques were meticulously applied to ensure replicability and comprehensive interpretation of the research findings.